Feto-maternal outcome in patients with HELLP and partial HELLP syndrome: a prospective 10 year study in Shri Guru Ram Rai Institute of Medical and Health Sciences, Uttarakhand, India - Tandon, Archna; Chaudhari, Priyanka; Gupta, Vineeta; Ramola, Monika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The acronym HELLP was coined by Loise Weinstein in 1982 to describe a syndrome consisting of hemolysis (H) elevated liver enzyme (EL) and low platelets (LP). The purpose of the study was to detect and evaluate the feto maternal outcome of HELLP and partial HELLP syndrome among preeclamptic patients. Methods: Study analyzed fetal and maternal outcome in 110 patients with HELLP syndrome and 89 patients with partial HELLP Syndrome and compared with 1100 patients of preeclampsia only. Results: 1210 patients were included in this study. Out of these patients HELLP syndrome, partial help syndrome and preeclampsia were 10% and 7.3% and 82.7%. The systolic BP, gestational age at admission and at delivery, hematological and biochemical parameters, vaginal delivery and type of anesthesia were significantly different in HELLP syndrome and partial HELLP syndrome than in pre eclampsia group. There was significant difference in perinatal outcome like birth weight, IUD, neonatal death and NICU-admissions. Eclampsia was significantly increased in HELLP syndrome and partial HELLP syndrome. Conclusions: HELLP and partial HELLP syndrome must be diagnosed as soon as possible. Partial HELLP and HELLP syndrome are equally dangerous. HELLP Syndrome is severe then preeclampsia in terms of maternal and perinatal outcome.